A Prospective Study of 3D Navigation-Guided Single-Position OLIF with Posterior Percutaneous Fixation - Bharat Rajendraprasad Dave; Mrugank Narvekar; Ajay Krishnan; Devanand Degulmadi; Ravi Ranjan Rai; Mirant Bharat Dave (Indian Spine Journal, 2025)
Background: Conventionally, OLIF is performed in the lateral decubitus position for the interbody cage placement, followed by repositioning the patient to the prone position for pedicle screw fixation. Intraoperative repositioning significantly increases the operative room utilization time and may increase complications. 3DCT-assisted navigation guidance enables posterior instrumentation in the lateral position, allowing completion of the procedure in a single position. We aimed to assess the accuracy of pedicle screw placement and the clinical efficiency of the single-position technique for OLIF using O-arm navigation. This study is a single-center prospective study. Materials and Methods: Consecutive patients presenting from July 2021 to February 2024, aged above 18 years, with single-level spondylolisthesis (L2–L5 levels) or stenosis who consented for the OLIF procedure were included in the study. The surgical details (blood loss, surgical timing, pedicle screw fixation time, and OLIF time) and complications were noted and analyzed. The pedicle screw accuracy was assessed using intraoperative 3DCT using O-arm. Results: Twenty-six patients with a mean age of 57 years (range: 33–70 years), including seven males and 19 females, underwent single-level OLIF in a single position. The mean surgical time was 182.53 ± 51.26 min (92–255 min). The mean OLIF time was 131.28 ± 44.02 (50–215 min), and the mean pedicle screw fixation time was 53.76 ± 22.06 (20–120 min). The mean blood loss during the surgery was 87.30 ± 98.65 mL (30–550 mL). The pedicle screw breach rate was 2.8% (3/104 screws), all <2 mm. Conclusion: Single-position OLIF performed with 3D navigation is a safe and efficient procedure.